Plan de marketing para mejorar la comercialización del vino de mortiño de la asociación de productores y comercializadores agropecuarios de Quinticusig del cantón Sigchos provincia de Cotopaxi en el periodo 2014. - Lutuala Catota, Luz Mercedes (2015)
The work developed a marketing plan for mortiño wine from agricultural Producers and Marketers Association of Quinticusig, Sigchos Canton, in order to improve the product image, it positions itself at the market, also to generate a productive activity inside the association and commercializing it is local level as national. This work research is consisting of elaborating mortiño wine on basis of adequate fermentation that would assess the main factors which determine the characteristics of the wines, taking into account the geographic, economic and social conditions of the place; the fermentation time of the wine was eight to twelve months. As for the assessment of mortiño production, it was conditioned by the fact which the fruit grow up exclusively of wild form the product is 100% nature, originally from Ecuadorian Highlands the mortiño is bearing only once a year, between September and November, in the paramos from Andes Mountains. The methodology used to development this work was: data collection functions and activities which are made in the association, from information collected which it will allow to get the final result in a marketing plan with its respective four P's that are applied, these will improve the functioning of the Association of Agricultural Producers and Traders of Quinticusig.